MEMPERTAHANKAN REPUTASI BISNIS BERKELANJUTAN MELALUI PENERAPAN SUSTAINABLE BRANDING: STUDI KASUS PADA ASIA PACIFIC RAYON - Harahap, Neshayani; Rumyeni, Rumyeni; Yazid, Tantri Puspita (Mediakom : Jurnal Ilmu Komunikasi, 2024)
This study examines the sustainable branding practices implemented by Asia Pacific Rayon (APR), a leading textile producer in Indonesia, in maintaining a strong business reputation. Based on stakeholder theory, which emphasizes the importance of engaging all stakeholders, this research explores APR's strategic focus on transparency and traceability across its supply chain. These practices reflect APR's commitment to ethical operations and alignment with global ESG standards to foster trust and competitiveness.Using a qualitative case study methodology, the study integrates stakeholder interviews, internal documents, and secondary data from APR and its parent company, APRIL. The key initiatives analyzed include stakeholder inclusiveness, communication transparency, a stakeholder-centered approach, and reputation management. Together, these efforts strengthen APR's reputation as a sustainable brand.The findings reveal that APR's alignment of sustainable branding strategies with ESG principles not only reinforces long-term trust but also ensures operational efficiency and resilience in the international market. These results affirm the relevance of stakeholder theory and expand on prior research regarding the integration of sustainability and branding practices.The study concludes that sustainable branding practices, when grounded in transparency and stakeholder engagement, are essential for building a credible and resilient business reputation. The insights contribute to the growing body of knowledge on sustainable branding and offer practical recommendations for industries aiming to integrate ESG principles into their operations.